ANALISIS PENCIPTAAN NILAI BERSAMA (VALUE CO-CREATION)DI PT GERBANG NTB EMAS - Sugiharto, Guruh; Sulhaini, Sulhaini; Saufi, Akhmad (Master of Management, Mataram University, 2017)
Sales of products achieved by PT Gerbang NTB Emas were not yet optimal. There weresome consumer obstacles and complaints that were occur. Among them were lack of production machineries and skilled manpower, quality of goods under specification and production time is not maximized. One way that can be done is to optimize value creation between consumers and producers. Value created together is expected to provide benefits for both parties. In this study aimed to analyze the process of value co-creation that occurs between the company (PT GNE) and its customers. The research method used is qualitative approach with data collection through interview, observation and documentation. The number of interviewees was five employees and one consumer. The collected data were analyzed with content analysis using NVivo software. The result of this research is that value co-creation at PT GNE can be explained through dialogue, access, risk management and transparency. Value can be interpreted as product innovation, service and strategic policy. By knowing these aspects, the company can maximize value creation along with consumers. The company gets sales profits and the consumer gets the desired product. Â Keywords: value, co-creation, dialogue, access, risk assessment, transparency, product innovation, service, strategic policy